A Case of Sublingual Dermoid Cyst: Extending the Limits of the Oral Approach - Ohta, Nobuo (Hindawi Publishing Corporation, 2012)
We present the case of a dermoid cyst with an oral and a submental component in a 21-year-old Japanese woman who presented with complaints of a mass in the oral cavity and difficulty in chewing and swallowing solid foods for about 2 years. MRI shows a 55 × 65 mm well-circumscribed cystic mass extending from the sublingual area to the mylohyoid muscle. Under general anesthesia and with nasotracheal intubation, the patient underwent surgical removal of the mass. Although the cyst was large and extending mylohyoid muscle, intraoral midline incision was performed through the mucosa overlying the swelling and the cyst was separated from the surrounding tissues with appropriate traction and countertraction and successfully removed without extraoral incision. Oral approach in surgical enucleation is useful procedure to avoid cosmetic problems in large and extending mylohyoid muscle cyst.